George W. Bush : evaluating the president at midterm - Hilliard, Bryan, 1957-; Lansford, Tom; Watson, Robert P., 1962- (SUNY series in the presidency., 2004)
"Bringing together presidential scholars, leading voices on the presidency, and former White House aides, this book provides a timely and thorough assessment of George W. Bush at the historic midpoint of his presidency. The book covers Bush's character and leadership style, domestic policy, foreign policy and the War on Terror, and the Bush administration. It concludes with a report card on the Bush presidency, whereby the President, his staff, and his legislative record are graded."--Jacket